ANALISIS USAHATANI PADI (Oryza sativa, Sp) SISTEM JAJAR LEGOWO 1:2 DENGAN PENGAIRAN TEKNIS DI DESA CINDOGO KECAMATAN TAPEN KABUPATEN BONDOWOSO - Ali Hasanah; Rini Purwatiningsih (FORAGRI : Jurnal Ilmu Pertanian, 2023)
Conclusion: a) The age factor has no significant effect on farmers’ income. b) The land area factor has a significant effect on the income of rice farmers. The wider the land they plant, the production will increase so that it will increase the income of farmers. c) The education factor has a significant effect on farmers’ income. d) The factor of the number of family members has no significant effect on farmers’ income. This is because there are more dominant factors such as land area. e) The experience factor has a significant effect on farmers’ income. This is because there are other factors that are more dominant, such as land area.